Clinical Characteristics of 76 Patients with IgG4-Related Hypophysitis: A Systematic Literature Review - Yujuan Li; Hua Gao; Zhen Li; Xinxin Zhang; Yizhi Ding; Fengao Li (International Journal of Endocrinology)
Background. IgG4-related hypophysitis (IgG4-RH) is a rare disease, and its prevalence remains unclear. In recent years, an increasing number of cases have been reported because of the increasing recognition of this disease. We aimed to summarize case reports of IgG4-RH and outline the clinical features and outcomes. Methods. We performed PubMed search of articles using the search terms “hypophysitis [AND] IgG4.” Consequently, only 54 English articles (76 cases) met Leporati’s diagnostic criteria. Results. Of the 76 cases, the ratio of men to women was 1.5 : 1, and the age at diagnosis was 54.1 ± 17.8 years. The median IgG4 concentration was 405.0 mg/dl. Anterior hypopituitarism, isolated central diabetes insipidus, and panhypopituitarism were observed in 14 (18.4%), 12 (15.8%), and 44 (57.9%) cases, respectively. The sequence of anterior hormone deficiency was as follows: gonadotropin (68.4%), ACTH (63.2%), TSH (59.2%), GH (48.7%), and prolactin (42.1%). The median number of involved organs was 1.5, and the lung (18.4%), retroperitoneum (17.1%), kidney (15.8%), submandibular glands (14.5%), and pancreas (13.2%) were the common involved organs. Elevated IgG4 concentration and normal IgG4 level were in 42 (76.4%) and 13 (23.6%) cases, respectively. Patients with elevated serum IgG4 concentration were older (60.9 ± 14.3 vs 45.6 ± 17.4, p=0.001) and male-prone (78.6% vs 40.4%, p=0.003) and had a susceptibility of multiple organ involvement (78.6% vs 35.0%, p=0.001) compared to those with normal serum IgG4 levels. Males were older at disease onset (61.5 ± 12.6 vs 42.9 ± 18.8, p<0.001) and had a higher IgG4 concentration (425.0 vs 152.5, p=0.029) and a greater number of involved organs (2.0 vs 0.0, p=0.001), while isolated hypophysitis was more prominent in female (63.3% vs 26.1%, p=0.001). Conclusion. In this review, we found that there were different characteristics between different genders. Patients with elevated serum IgG4 level in terms of some clinical features were also different from those with normal serum IgG4 level. However, the data in this review were limited by bias and confounding. Further clinical studies with larger sample sizes are warranted.